Impact of behavior and mood of people with specific needs on quality and feasibility of teledentistry: A five years retrospective study - Camille Inquimbert; Céline Sabourin; Nicolas Sepashvili; Jean Valcarcel; Abid Bossouf; Nicolas Giraudeau (Digital Health, 2024)
Background The e-DENT program, initiated by Montpellier University Hospital's Department of Dentistry, seeks to enhance dental care access for individuals with special needs through teledentistry. This five-year retrospective study focuses on the program's impact, particularly assessing patients’ mood and behavior during telemedicine dental examinations and the influence of these factors on diagnostic quality and feasibility. Methods This retrospective, multicentric observational study analyzed data from January 1, 2018, to April 24, 2023, involving residents of medico-social institutions who participated in the e-DENT program. The study utilized a scoring system based on the PANAS scale, which is used to brief measures of positive and negative affects. We aimed to evaluate mood and behavior. The statistical analysis was conducted using R software, incorporating mixed logistic and linear regressions to assess the impact of various factors on patient behavior, mood scores, and the quality and feasibility of diagnoses. Findings The study included 682 patients, revealing that the majority exhibited cooperative behavior during their telemedicine consultations, with a median mood score of 2.5. Analysis showed a significant improvement in mood scores from the first to subsequent consultations. The mood score positively correlated with diagnostic feasibility and negatively with visit duration. Specific factors such as type of disability, fear of dental instruments, and patient cooperation significantly influenced the quality of videos taken and the feasibility of diagnoses. Facilities catering to different disability types showed varied mood scores, suggesting tailored approaches may be necessary. Interpretation The findings underscore the efficacy of teledentistry in providing dental care to individuals with special needs, highlighting the importance of patient mood and behavior in improving diagnostic outcomes. The study suggests that teledentistry can be a well-accepted and effective mode of dental care delivery for this patient group, with implications for optimizing telemedicine practices in medico-social settings.